Urban indoor airborne antibiotic resistance genes: Role of antibiotic use and outdoor air pollution - Hesham Amin; Tina Šantl-Temkiv; Inge M.Wouters; Ane Johannesen; Torben Sigsgaard; Vivi Schlünssen; Andrei Malinovschi; Hulda Thorarinsdottir; Randi J. Bertelsen (Science of The Total Environment, 2026)

Mortality impacts of air pollution and greenness: real-world and counterfactual exposure scenarios in seven Northern European cities - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Andrei Malinovschi; et al. (Environmental Research, 2026)

Indoor airborne bacterial communities and adult lung health: A cross-sectional study - Hesham Amin; Christine Cramer; Kai Finster; Francisco Gomez Real; Thorarinn Gislason; Mathias Holm; Christer Janson; Nils Oskar Jögi; Rain Jogi; Andrei Malinovschi; Lars Modig; Dan Norbäck; et al. (International Journal of Hygiene and Environmental Health, 2026)

Associations of parental air pollution and greenness exposures with offspring asthma outcomes - Robin M. Sinsamala; Alessandro Marcon; Randi J. Bertelsen; Simone Accordini; Jørgen Brandt; Lise M. Frohn; Camilla Geels; Thorarinn Gislason; Mathias Holm; Christer Janson; Andrei Malinovschi; Iana Markevych; et al. (Environmental Research, 2025)

Long-term exposure to air pollution and greenness in association with respiratory emergency room visits and hospitalizations: The Life-GAP project - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Iana Markevych; et al. (Environmental Research, 2025)

Persistent organic pollutants among seafood processing workers in West Greenland - Maria Wielsøe; Manhai Long; Jakob Hjort Bønløkke; Rossana Bossi; Niels E. Ebbehøj; Kurt Rasmussen; Torben Sigsgaard; Eva Cecilie Bonefeld-Jørgensen (International Journal of Hygiene and Environmental Health, 2025)

Associations of long-term exposure to air pollution and greenness with incidence of chronic obstructive pulmonary disease in Northern Europe: The Life-GAP project - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Iana Markevych; et al. (Environmental Research, 2024)

Gas cooking indoors and respiratory symptoms in the ECRHS cohort - Holly Pan; Debbie Jarvis; James Potts; Lidia Casas; Dennis Nowak; Joachim Heinrich; Judith Garcia Aymerich; Isabel Urrutia; Jesus Martinez-Moratalla; José-Antonio Gullón; Antonio Pereira-Vega; Chantal Raherison; et al. (International Journal of Hygiene and Environmental Health, 2024)

Prenatal exposure to nitrosatable drugs and timing of puberty in sons and daughters: A nationwide cohort study - Pernille Jul Clemmensen; Nis Brix; Jörg Schullehner; Andreas Ernst; Lea Lykke Harrits Lunddorf; Anne Ahrendt Bjerregaard; Thorhallur Ingi Halldorsson; Sjurdur Frodi Olsen; Birgitte Hansen; Leslie Thomas Stayner; Henrik Albert Kolstad; Torben Sigsgaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Medium term moderate to low-level air pollution exposure is associated with higher C-reactive protein among healthy Danish blood donors - Bertram Kjerulff; Henriette Thisted Horsdal; Kathrine Kaspersen; Susan Mikkelsen; Khoa Manh Dinh; Margit Hørup Larsen; Sisse Rye Ostrowski; Henrik Ullum; Erik Sørensen; Ole Birger Pedersen; Mie Topholm Bruun; Kaspar René Nielsen; et al. (Environmental Research, 2023)

Prenatal Exposure to Nitrate in Drinking Water and Adverse Health Outcomes in the Offspring: a Review of Current Epidemiological Research - Pernille Jul Clemmensen; Jörg Schullehner; Nis Brix; Torben Sigsgaard; Leslie Thomas Stayner; Henrik Albert Kolstad; Cecilia Høst Ramlau-Hansen (Current Environmental Health Reports, 2023)
Purpose of Review Recently, several epidemiological studies have investigated whether prenatal exposure to nitrate from drinking water may be harmful to the fetus, even at nitrate levels below the current World Health Organization drinking water standard. The purpose of this review was to give an overview of the newest knowledge on potential health effects of prenatal exposure to nitrate. Recent Findings We included 13 epidemiological studies conducted since 2017. Nine studies investigated outcomes appearing around birth, and four studies investigated health outcomes appearing in childhood and young adulthood. Summary The reviewed studies showed some indications of higher risk of preterm delivery, lower birth weight, birth defects, and childhood cancer related to prenatal exposure to nitrate. However, the numbers of studies for each outcome were sparse, and some of the results were conflicting. We suggest that there is a need for additional studies and particularly for studies that include information on water consumption patterns, intake of nitrate from diet, and intake of nitrosatable drugs.

Optimization of bacterial DNA and endotoxin extraction from settled airborne dust - Hesham Amin; Ian P.G. Marshall; Randi J. Bertelsen; Inge M. Wouters; Vivi Schlünssen; Torben Sigsgaard; Tina Šantl-Temkiv (Science of The Total Environment, 2023)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Airborne Cladosporium and Alternaria spore concentrations through 26 years in Copenhagen, Denmark - Yulia Olsen; Carsten Ambelas Skjøth; Ole Hertel; Karen Rasmussen; Torben Sigsgaard; Ulrich Gosewinkel (Aerobiologia, 2020)

Regional variation in airborne Alternaria spore concentrations in Denmark through 2012–2015 seasons: the influence of meteorology and grain harvesting - Yulia Olsen; Ulrich Bay Gosewinkel; Carsten Ambelas Skjøth; Ole Hertel; Karen Rasmussen; Torben Sigsgaard (Aerobiologia, 2019)

Grain harvesting as a local source of Cladosporium spp. in Denmark - Yulia Olsen; Tanja Begovic; Carsten Ambelas Skjøth; Karen Rasmussen; Ulrich Gosewinkel; Ole Hertel; Torben Sigsgaard (Aerobiologia, 2019)

Systematic Review of Respiratory Health Among Dairy Workers - Stephen J. Reynolds; Matthew W. Nonnenmann; Ioannis Basinas; Margaret Davidson; Lena Elfman; John Gordon; Shelley Kirychuck; Sue Reed; Joshua W. Schaeffer; Marc B. Schenker; Vivi Schlünssen; Torben Sigsgaard (Journal of Agromedicine, 2013)

Land‐atmosphere exchange of methane from soil thawing to soil freezing in a high‐ A rctic wet tundra ecosystem - Torbern Tagesson; Meelis Mölder; Mikhail Mastepanov; Charlotte Sigsgaard; Mikkel P. Tamstorf; Magnus Lund; Julie M. Falk; Anders Lindroth; Torben R. Christensen; Lena Ström (Global Change Biology, 2012)
The land‐atmosphere exchange of methane ( CH 4 ) and carbon dioxide ( CO 2 ) in a high‐ A rctic wet tundra ecosystem ( R ylekærene) in Z ackenberg, north‐eastern G reenland, was studied over the full growing season and until early winter in 2008 and from before snow melt until early winter in 2009. The eddy covariance technique was used to estimate CO 2 fluxes and a combination of the gradient and eddy covariance methods was used to estimate CH 4 fluxes. Small CH 4 bursts were observed during spring thawing 2009, but these existed during short periods and would not have any significant effect on the annual budget. Growing season CH 4 fluxes were well correlated with soil temperature, gross primary production, and active layer thickness. The CH 4 fluxes remained low during the entire autumn, and until early winter. No increase in CH 4 fluxes were seen as the soil started to freeze. However, in autumn 2008 there were two CH 4 burst events that were highly correlated with atmospheric turbulence. They were likely associated with the release of stored CH 4 from soil and vegetation cavities. Over the measurement period, 7.6 and 6.5 g C m −2 was emitted as CH 4 in 2008 and in 2009, respectively. R ylekærene acted as a C source during the warmer and wetter measurement period 2008, whereas it was a C sink for the colder and drier period of 2009. Wet tundra ecosystems, such as R ylekærene may thus play a more significant role for the climate in the future, as temperature and precipitation are predicted to increase in the high‐ A rctic.

Allergy in bakers’ apprentices and factors associated to non-participation in a cohort study of allergic sensitization - Tina Skjold; Sven C. Nielsen; Katja Adolf; Hans Jürgen Hoffmann; Ronald Dahl; Torben Sigsgaard (International Archives of Occupational and Environmental Health, 2007)

Respiratory symptoms and ex vivo cytokine release are associated in workers processing herring. - Jakob Hjort Bnlkke; Mads Thomassen; Sven Viskum; yvind Omland; Eva Bonefeld-Jrgensen; Torben Sigsgaard (International Archives of Occupational and Environmental Health, 2004)